2020
DOI: 10.1016/j.omtm.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Superior Expansion and Cytotoxicity of Human Primary NK and CAR-NK Cells from Various Sources via Enriched Metabolic Pathways

Abstract: Clinical success of chimeric antigen receptor (CAR) T cell immunotherapy requires the engineering of autologous T cells, which limits the broader implementation of CAR cell therapy. The development of allogeneic and universal cell products will significantly broaden their application and reduce costs. Allogeneic natural killer (NK) cells can be used for universal CAR immunotherapy. Here, we develop an alternative approach for the rapid expansion of primary NK and CAR-NK cells with superior expansion capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 90 publications
2
54
0
Order By: Relevance
“…Where necessary, patient consent was obtained before obtaining clinical samples. NK and CAR-NK cells were expanded with 100-Gy irradiated 721.221-mIL21 cells and supplemented with 200 U/mL IL-2 and 5 ng/mL IL-15 (Peprotech, Rocky Hill, CT, USA) 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Where necessary, patient consent was obtained before obtaining clinical samples. NK and CAR-NK cells were expanded with 100-Gy irradiated 721.221-mIL21 cells and supplemented with 200 U/mL IL-2 and 5 ng/mL IL-15 (Peprotech, Rocky Hill, CT, USA) 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Less differentiated NK cells which display a memory-like phenotype can also be generated by ex vivo expansion using 721,221 feeder cells with membrane-bound IL-21 [166]. Critically, these cells upregulated genes related to glucose and amino acid metabolism, including amino acid transporter SLC7A5 and the transcription factor c-Myc, which are critical for NK cell function [167].…”
Section: Memory-like Nk Cellsmentioning
confidence: 99%
“…Recent clinical trials testing cancer immunotherapies have shown promising results for treating infectious diseases 14 . One of crucial barriers to using primary NK cells for immunotherapy is the difficulty in obtaining an adequate number of NK cells from peripheral blood or cold blood before expansion 18 . We have optimized the NK cell expansion technology to buffer this potential limitation.…”
Section: Discussionmentioning
confidence: 99%
“…1b). 293T cells were transfected with a combination of plasmids containing CR3022-CAR in the SFG backbone, RDF, and PegPam3, as previously described 17,18 . The SFG retrovirus particles were used to transduce NK-92MI cells.…”
Section: Generation Of Cr3022-car-nk-92mi Cellsmentioning
confidence: 99%